The Ideology of Home Ownership - Ronald, R. author. aut Link
XII, 282 p.
Keywords: Demand for owner-occupied housing has expanded dramatically across modern-industrialized societies in recent years leading to volatile increases in residential property values. This book explores the rise of modern home-ownership as a cultural, socio-political and ideological phenomenon.